Interplay between SARS-CoV-2 and Cancer: Plausible Risk Factors, Cellular Immune Responses, Cancer Directed Therapy- Current Challenges - Ray, Suman K.; Mukherjee, Sukhes (Infectious Disorders - Drug Targets, 2023)
COVID-19 has created tremendous societal upheaval, resulting in a global overhaul of healthcare systems. According to new evidence, the COVID-19 pandemic has the potential to aggravate pre-existing inequities, particularly among cancer patients. The COVID-19 pandemic has had a disproportionately negative impact on cancer patients. The unfavorable outcomes in cancer patients who contract COVID-19, the impact of the COVID-19 pandemic on cancer care delivery, and the significant disruption of cancer research are all examples of this consequence. On the other hand, patients with cancer are a diverse group, and new research has identified characteristics that allow for risk categorization of cancer patients to optimize care. Variable access to telemedicine, timely diagnosis, and treatment access are all possible drivers of unequal cancer survival as a result of the epidemic. Despite oncology associations presenting guidelines on cancer care during the pandemic, the magnitude of potential therapy advantages, therapeutic purpose, and access to care all play a role in prioritizing cancer medicines. This review focuses on evidence related to COVID-19 and cancer, such as the molecular interactions between the two diseases and practical therapeutic suggestions for cancer patients during the pandemic. We also explore the pandemic's possible long-term influence on cancer care due to its negative impact on cancer research, as well as biological discoveries from the cancer research community that could aid in the development of novel therapeutics for all COVID-19 patients.
Keywords: patient care